2007
DOI: 10.1016/j.nucmedbio.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping of breast cancer via intradermal administration of Lymphoseek

Abstract: Lymphoseek™ is a molecular imaging agent specifically designed for sentinel lymph node (SLN) mapping. We conducted a Phase I trial which measured the injection site clearance and sentinel lymph node accumulation after a single intra-dermal injection of Lymphoseek or [ 99m Tc]sulfur colloid protocol. Ten patients with breast cancer participated in this study. Five patients received an intradermal administration of 1.0 nmole of 99m Tc-labeled Lymphoseek and five patients received an intra-dermal administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
0
20
1
Order By: Relevance
“…Faster injection site clearance and equivalent sentinel node uptake were similarly demonstrated in another phase I trial also in breast cancer patients but with an intradermal injection technique. The intradermal injection, however, did not exhibit a faster clearance half-time than peritumoral/subdermal injection (18). A similar phase I trial by the same group, performed on melanoma patients, also found that 99m Tc-tilmanocept demonstrated faster injection site clearance and equivalent primary sentinel node uptake when compared with filtered 99m Tc-SC (7).…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…Faster injection site clearance and equivalent sentinel node uptake were similarly demonstrated in another phase I trial also in breast cancer patients but with an intradermal injection technique. The intradermal injection, however, did not exhibit a faster clearance half-time than peritumoral/subdermal injection (18). A similar phase I trial by the same group, performed on melanoma patients, also found that 99m Tc-tilmanocept demonstrated faster injection site clearance and equivalent primary sentinel node uptake when compared with filtered 99m Tc-SC (7).…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…A protocol using a single intradermal injection of Lymphoseek [12] in five breast cancer patients produced a percent-of-injected dose of 1.1±0.5% when the time interval ranged from 3.4 to 6.1 h. This was lower, but not statistically significant ( P =.76), than the 2-day protocol where the sentinel lymph node uptake was 1.5±1.7% and the time interval ranged from 19.4 to 27.1 h. Sentinel lymph node uptake of filtered TcSC [12] was 2.5±4.9% when the uptake time interval ranged from 3.5 to 7.3 h. This was lower than 3.5±3.1%, the uptake achieved by unfiltered TcSC when the uptake time interval ranged from 18.0 to 25.9 h. Although noteworthy, the increase in colloid SLN accumulation achieved by the 2-day protocol was not statistically significant. This is mainly due to the high biological variation in subject lymphatic flow and function.…”
Section: Discussionmentioning
confidence: 99%
“…This accounts for the high relative error of ±167%. The clearance rate constant of filtered TcSC [12] using the same injection protocol exhibited a mean and standard deviation of 0.029 ±0.021 h −1 . The lowered relative error of ±72% occurred because only one of five studies was assigned a zero clearance rate due to a positive slope in the time–activity curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Though radioactive colloids are the most used tracers, some researchers propose alternative radiopharmaceuticals. 10 LS is generally performed on planar views; some studies 11,12 suggest more complex LS methods, including single-photon emission computed tomography (SPECT) and triangulations. Studies on GP addressed to improve this device and to standardize its performances are also available.…”
Section: Introductionmentioning
confidence: 99%